Particularities of anesthesia in felines (Research, Society and Development, 2021)
Anesthetic complications appear relatively rare, though recent work suggests they are more common in cats than dogs. The anesthetic particularities observed in felines may be directly related to the higher rates of complications observed in these animals. Important aspects in this species, including perianesthetic anxiety and stress, perianesthetic monitoring, the role of underlying diseases as well as the correct use of anesthesia equipment and total intravenous anesthesia, are often overlooked by anesthetists. Therefore, the study aimed to review and discuss the main anesthetic particularities in felines, enabling the veterinarian to understand the most important aspects of anesthesia in these patients, avoiding perioperative complications associated with pre-existing diseases, anesthetic agents, airway control, management and monitoring. These data can help veterinarians to care for the patient under anesthesia and direct more attention to the assessment and treatment of the patient before, during and after the procedure.